The Spear: The Main Weapon in Iranian Martial Tradition (Revista de Artes Marciales Asiáticas, 2012)
In martial tradition, spears and lances have always played a very important role as main weapons on the battlefield, as exemplified through Iranian military history. Its reach and cheap production were important factors for establishing formations of soldiers equipped with spears and lances. Additionally, the combat techniques of spears and lances were relatively easy and one could learn the techniques of spearfighting and lancefighting much easier than other weapons, such as swords. The first part of the article describes some types of spears and lances that were used in the Islamic period of Iran. Then the method of carrying a spear/lance is analyzed and additionally some offensive techniques, feinting techniques, attacking techniques to the animal carrying the opponent, and defensive techniques using spears/lances are described as documented by Persian manuscripts.